Diagnostic value of combined detection of pepsinogen, gastrin-17, and 13C-urea breath test in Helicobacter pylori-associated chronic gastritis in children: a multivariate analysis - Gao, Yiyun; Liu, Chuangui; Ouyang, Kaishi; Li, Siqi; Huang, Weilin (Frontiers in Pediatrics, 2025)
BackgroundThis study evaluated the diagnostic efficacy of combining pepsinogen (PG I/II), gastrin-17 (G-17), and 13C-urea breath test (13C-UBT) for chronic gastritis in children using logistic regression and receiver operating characteristic (ROC) analysis.MethodsBetween June 2018 and August 2023, 65 children with chronic gastritis and 50 healthy controls participated. Inclusion criteria for both groups: Age 6–12 years, chronic gastritis confirmed by endoscopy and histopathology for the gastritis group, and absence of GI symptoms for the control group. Exclusion criteria: Severe cardiopulmonary dysfunction, gastroduodenal surgery, recent use of PPIs/antibiotics, and H. pylori eradication therapy. Serum levels of PG I, PG II, and G-17 were determined by ELISA, and 13C-UBT was used to detect Helicobacter pylori (Hp) infection.ResultsCombined detection showed significantly higher positive rates than individual PG I/II or G-17 tests (P < 0.05), but similar to 13C-UBT alone. Chronic gastritis patients had elevated PG I, and G-17 levels compared to controls (P < 0.05). Multivariate analysis identified PG I (OR = 1.048, P = 0.014), G-17 (OR = 1.943, P < 0.001), and 13C-UBT positivity (OR = 17.417, P < 0.001) as significant predictors. ROC analysis revealed AUCs of 0.692 (PG I), 0.594 (PG II), 0.782 (G-17), 0.808 (13C-UBT), and 0.844 (combined), with sensitivity ≥90.8% and specificity >78%.ConclusionThe combined detection of PG I/II, G-17, and 13C-UBT shows strong diagnostic potential for Helicobacter pylori-associated chronic gastritis in children, offering enhanced diagnostic accuracy and a non-invasive tool for early screening and intervention.